PELATIHAN PENGELOLAAN KEUANGAN UNTUK MENINGKATKAN KEMAMPUAN MENGELOLA UTANG DAN INVESTASI DI KALANGAN MASYARAKAT - Etty Harya Ningsi; Tri Auri Yanti; A’an Nurhadi (LPPM UNINUS, 2024)
The issue of financial management, particularly in terms of debt and investment, presents a significant challenge for many individuals in Indonesia. A large portion of the population lacks sufficient understanding of personal finance, debt, and investment management, which leads to long-term financial difficulties. This study aims to implement financial management training focused on debt and investment management, with the goal of improving the community's ability to manage finances more wisely and effectively. The training was conducted in Lubuk Pakam District, with participants from diverse backgrounds. The results of the training showed a significant improvement in participants' understanding of healthy debt management strategies and the fundamentals of profitable investment. It is expected that this training will have a positive impact on the long-term economic well-being of the community.